Design of people evacuation from rooms and buildings - Papinigis, Vytautas; Geda, Edgaras; Lukošius, Kęstutis (Journal of Civil Engineering and Management, 2010)
There is a fire hazard in many civil buildings or engineering structures. Analysis of people evacuation time from the room or building is an important part of the designing process. Nevertheless, analysis of human behaviour in fire conditions is very complicated. Various factors should be evaluated, physical and even psychical, influencing safe evacuation of people from buildings. The analytical and calculating methods created are intended for analysis of people evacuation in fire conditions. Unfortunately, use of complicated calculations for determination of people evacuation requires too many resources; therefore, their application is limited. The calculation method for people evacuation presented in this paper is based on dependencies of the physical characteristics of people stream (density, intensity, movement speed) on people movement manner. The time required to evacuate people from people gathering room and building is determined in the numerical illustration of the method application. The article presents the comparison of simple calculation method and modeling with FDS+Evac software results of time for safe evacuation of people from rooms and buildings. Published Published Online: 24 Jun 2011